The use of live-yeast suspension in beef cattle rations. - Richardson, D.; Baker, F.H.; Harris, J.O.; Smith, E.F.; Cox, R.F.; Bowman, O.M. (Kansas Agricultural Experiment Station, 2011)
The rumen, or paunch, of cattle and sheep normally contains innumerable microorganisms. It has long been recognized that these microscopic organisms help break down complex carbohydrates such as fiber and help synthesize nutrients for the host animal. The efficiency of utilization of rations fed to cattle and sheep is largely determined by the proper balance of these microorganisms in the rumen and a supply of certain basic nutrients such as protein, minerals, and readily available energy. Two strains of live yeast were used as an additive in this experiment to study (1) their value in wintering and fattening rations of steer calves (2) their effect upon digestion and (3) any carryover effect from wintering to grazing.
Keywords: Beef; Live-yeast; Microorganisms; Rations